Capillary-gravity waves on the interface of two dielectric fluid layers under normal electric fields. Issue 3 (5th June 2020) - Doak, A; Gao, T; Vanden-Broeck, J -M; Kandola, J J S
Summary: In this article, we consider capillary-gravity waves propagating on the interface of two dielectric fluids under the influence of normal electric fields. The density of the upper fluid is assumed to be much smaller than the lower one. Linear and weakly nonlinear theories are studied. The connection to the results in other limit configurations is discussed. Fully nonlinear computations for travelling wave solutions are achieved via a boundary integral equation method. Periodic waves, solitary waves and generalised solitary waves are presented. The bifurcation of generalised solitary waves is discussed in detail.